2015
DOI: 10.1021/acsami.5b06223
|View full text |Cite
|
Sign up to set email alerts
|

Carrier Transport at Metal/Amorphous Hafnium–Indium–Zinc Oxide Interfaces

Abstract: In this paper, the carrier transport mechanism at the metal/amorphous hafnium-indium-zinc oxide (a-HIZO) interface was investigated. The contact properties were found to be predominantly affected by the degree of interfacial reaction between the metals and a-HIZO; that is, a higher tendency to form metal oxide phases leads to excellent Ohmic contact via tunneling, which is associated with the generated donor-like oxygen vacancies. In this case, the Schottky-Mott theory is not applicable. Meanwhile, metals that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 53 publications
(111 reference statements)
0
7
0
Order By: Relevance
“…Amorphous and polycrystalline mixed-metal oxides are employed in applications that range from thin-film transistors and solar cells, , to catalysts for reactions including hydrocarbon oxidation, hydrogen production via water-splitting, and oxygenate reforming. The versatility of mixed-metal oxide materials is due to their wide range of electronic properties, which depend on chemical composition and physical structure (e.g., crystalline vs amorphous). For example, the band gap of bismuth-containing mixed-transition-metal oxides, used for oxidation catalysis, varies based on the identity of the transition metal(s) due to the dependence of the lowest unoccupied energy levels on empty d-orbitals .…”
Section: Introductionmentioning
confidence: 99%
“…Amorphous and polycrystalline mixed-metal oxides are employed in applications that range from thin-film transistors and solar cells, , to catalysts for reactions including hydrocarbon oxidation, hydrogen production via water-splitting, and oxygenate reforming. The versatility of mixed-metal oxide materials is due to their wide range of electronic properties, which depend on chemical composition and physical structure (e.g., crystalline vs amorphous). For example, the band gap of bismuth-containing mixed-transition-metal oxides, used for oxidation catalysis, varies based on the identity of the transition metal(s) due to the dependence of the lowest unoccupied energy levels on empty d-orbitals .…”
Section: Introductionmentioning
confidence: 99%
“…Angle-resolved HAXPES analysis revealed that V O in IGZO:H was much lower than that in IGZO, especially in the region near the film surface (Figure e). Both the increase of ϕ b and the decrease of V O at the Ag x O/IGZO:H interface reduce the tunneling current through the junction barrier due to trap-assisted tunneling. ,,, Moreover, the HAXPES analysis also revealed that the density of near-CBM states in IGZO:H was lower than that in IGZO after annealing at a T ann of 150 °C. The reduction of near-CBM states in IGZO:H also contributed to reduce the tunneling current in the SDs.…”
Section: Resultsmentioning
confidence: 98%
“…Additionally, oxygen-poor regions are formed by the reduction of IGZO when a metal comes in contact with it . These surface and interface defect states increase the carrier concentration of IGZO and lead to the ohmic behavior . This is why the AOS-based SDs show mostly ohmic or near-ohmic, independent of the metal used .…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic–organic halide perovskites exhibit intrinsic properties, such as appropriate electronic structures and small exciton binding energy, [ 1–8 ] making it an attractive absorber material in photovoltaics. Low fabrication cost and high efficiencies (currently certified as 25.5% [ 9 ] ) of perovskite solar cells (PSCs) make it promising for commercialization as either single‐junction devices or in tandems with lower bandgap absorber solar cells, including silicon, chalcogenides, and tin‐related materials.…”
Section: Figurementioning
confidence: 99%